Anti-cyclooxygenase, anti-glycation, and anti-skin aging effect of Dendrobium officinale flowers’ aqueous extract and its phytochemical validation in aging - Zhou, Huiji; Zhou, Luxian; Li, Bo; Yue, Rongcai (Frontiers in Immunology, 2023)
The information available in the literature concerning beneficial effects of Dendrobium officinale flowers for the skin is limited. Therefore, the present study aimed to investigate the in vitro biological potency of its aqueous extract and to screen its active components. The aqueous extract of flowers of D. officinale was found to have potential antioxidant capacity (through 2,2-diphenyl-1-picrylhydrazyl [DPPH], 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) [ABTS], ferric reducing ability of plasma [FRAP], and intracellular reactive oxygen species [ROS] level analyses in primary human epidermal keratinocytes, anti-cyclooxygenase2 (COX-2) effect, anti-glycation potency, and anti-aging effects. A total of 34 compounds were identified using ultra-performance liquid chromatography-electrospray ionisation-quadrupole-time-of-flight-mass spectrometry (UPLC-ESI-QTOF-MS/MS). Online ABTS radical UPLC-photodiode array detection (PDA) analysis demonstrated that 1-O-caffeoyl-β-D-glucoside, vicenin-2, luteolin-6-C-β-D-xyloside-8-C-β-D-glucoside, quercetin-3-O-sophoroside, rutin, isoquercitrin, and quercetin 3-O-(6’’-O-malonyl)-β-D-glucoside are the major potential antioxidants. In addition, 16 components were further analysed using antioxidant assays (DPPH, ABTS, and FRAP); COX-2 and AGE inhibitory activities were assessed. All selected compounds exerted significant ABTS radical scavenging ability and effective AGE suppressive activities. However, only certain compounds, such as rutin and isoquercitrin, displayed selective and significant antioxidant abilities, as shown by DPPH and FRAP, as well as potent COX-2 inhibitory capacity, whereas the remaining compounds displayed relatively weak or no effects. This indicates that specific components contributed to different functionalities. Our findings justified that D. officinale and its active compound targeted related enzymes and highlighted its potential application in anti-aging.